Preparation of Financial Statements for UMKM Cafe Kenza & Billiard Gowa through Audit Assistance for the Inventory, Warehousing, and Accounts Payable Cycles - Ismail Badollahi; Wahyuni; Nurtisatul Mukarramah; Putri Latifah Ramadani Lewa; Burhan; DM Triaryadi Hasanuddin; Elly Haerunnisa (Masterpiece, 2026)
Inadequate financial management and internal control remain common obstacles for many Micro, Small, and Medium Enterprises (MSMEs), including Cafe Kenza & Billiard. This situation results in incompletely documented transaction recording, uncontrolled inventory management, and financial reports not being prepared in accordance with accounting principles. Therefore, this Community Service activity aims to evaluate internal controls in the inventory, warehousing, and accounts payable payment cycles while also assisting in the preparation of simple financial reports. The activity was carried out on July 8–10, 2026, at Cafe Kenza & Billiard, Gowa Regency, using observation, interviews, documentation, and the Internal Control Questionnaire (ICQ). The data obtained were analyzed as the basis for preparing a list of accounts, general journal, ledger, trial balance, and income statement based on available transaction evidence. The results of the activity showed that internal control was still weak, indicated by the absence of an organizational structure, stock cards, inventory mutation recording, and adequate transaction evidence documentation. Nevertheless, the mentoring succeeded in increasing the owner's understanding of the importance of internal control and producing a more structured simple financial report. This activity demonstrates that accounting mentoring and internal control evaluation play a crucial role in improving the quality of financial governance and accountability in MSMEs.